Proceedings of the FSE/SDP Workshop on Future of Software Engineering Research 2010
DOI: 10.1145/1882362.1882365
|View full text |Cite
|
Sign up to set email alerts
|

Software economies

Abstract: Software construction has typically drawn on engineering metaphors like building bridges or cathedrals, which emphasize architecture, specification, central planning, and determinism. Approaches to correctness have drawn on metaphors from mathematics, like formal proofs. However, these approaches have failed to scale to modern software systems, and the problem keeps getting worse.We believe that the time has come to completely re-imagine the creation of complex software, drawing on systems in which behavior is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Bacon et al proposed viewing software development as an economy. They present software estimation as an example, where project managers are rewarded by accurate estimations and developers benefit from quick feature delivery [34]. Following that vision, Rao et al suggested a software maintenance game where developers compete by submitting deep or shallow fixes, comparable with the fixkludge scenario we presented in Section 4 [35].…”
Section: A Survey Of Game Theory Applied To Software Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacon et al proposed viewing software development as an economy. They present software estimation as an example, where project managers are rewarded by accurate estimations and developers benefit from quick feature delivery [34]. Following that vision, Rao et al suggested a software maintenance game where developers compete by submitting deep or shallow fixes, comparable with the fixkludge scenario we presented in Section 4 [35].…”
Section: A Survey Of Game Theory Applied To Software Engineeringmentioning
confidence: 99%
“…They address this by using mean field games, which support a large number of players. Some interesting topics covered by these authors are mechanism design [32,34,35], data-based validation [31] and game abstraction [34]. However, they studied each of these topics in isolation.…”
Section: A Survey Of Game Theory Applied To Software Engineeringmentioning
confidence: 99%
“…Note that these domination definitions imply that the variation of the random variable around its mean is dominated in a moment generating function sense by that of a Gaussian or Poisson random variable. 3 Such a property is satisfied by many distributions including Poisson and binomial that are used to model arrival processes for many systems, e.g., telephone networks, internet, call centers, and some freelance markets [5], [6]. It is not hard to show that sub-Gaussian distributions (standard in machine learning [36]) that are symmetric around their mean, are Gaussian-dominated.…”
Section: Algorithm 2 Greedyagent Allocationmentioning
confidence: 99%
“…The combined force of the trends described earlier has been the emergence of new models of work including: globally dispersed teams in firms [18], outsourcing, crowdsourcing [20], information factories [8], virtual enterprises [13], crossenterprise collaborations [17], open source, social production [5], and asset reuse [2].…”
Section: The Changing Nature Of Work and Workforcementioning
confidence: 99%